Peran Fintech Peer to Peer Lending Syariah dalam Meningkatkan Akses Pembiayaan UMKM di Indonesia (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This paper examines the role of Fintech Peer-to-Peer (P2P) Lending Sharia in enhancing financing access for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The objective is to explore how P2P Lending Sharia facilitates MSMEs in securing necessary capital and offers investment opportunities in compliance with Sharia principles. The methodology involves a review of existing literature and regulatory frameworks, including the principles outlined by the OJK and DSN MUI. Findings reveal that P2P Lending Sharia provides an efficient, cost-effective, and accessible financial solution, enabling MSMEs to expand their market reach and improve business capacity. It also offers investors a Sharia-compliant alternative to traditional financing. The significance of these findings lies in the potential of P2P Lending Sharia to support MSME growth, strengthen the real sector, and contribute to national economic development, while adhering to Islamic financial principles. This innovation is essential in bridging the financing gap and fostering economic inclusivity